Asymptotics of the general solution to a linear singularly perturbed system of second-order differential equations with degeneracy - Yakovets, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
By using the perturbation methods and Newton diagrams, we study the structure and construct the asymptotics of the general solution to a linear singularly perturbed system of ordinary second-order differential equations in the case where the matrix by the higher derivative is degenerate.